2003
DOI: 10.1038/sj.gene.6364021
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIB gene polymorphisms in Japanese periodontitis patients

Abstract: Human type II low-affinity receptor for immunoglobulin G (FcgRII) constitutes a clustered gene family consisting of FcgRIIA, IIB and IIC genes. FcgRIIB is unique in its ability to transmit inhibitory signals in B cells via immunoreceptor tyrosine-based inhibitory motif (ITIM). B-cell activation and subsequent elevated production of IgG are the immunopathological features of inflammatory disease such as periodontitis. To determine whether an association with periodontitis susceptibility exists, genetic polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
1
37
0
2
Order By: Relevance
“…In this study, we demonstrated an overrepresentation of FcγRIIB‐232T allele in patients with SLE, periodontitis, and both diseases compared to healthy controls. FcγRIIB‐232I/T polymorphism was associated with susceptibility to SLE 16 or aggressive periodontitis 17 in Japanese patients. Our results failed to indicate a significant difference in the FcγRIIB‐232T frequency between SLE patients with and without periodontitis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, we demonstrated an overrepresentation of FcγRIIB‐232T allele in patients with SLE, periodontitis, and both diseases compared to healthy controls. FcγRIIB‐232I/T polymorphism was associated with susceptibility to SLE 16 or aggressive periodontitis 17 in Japanese patients. Our results failed to indicate a significant difference in the FcγRIIB‐232T frequency between SLE patients with and without periodontitis.…”
Section: Discussionmentioning
confidence: 97%
“…FcγRIIB‐232I/232T genotypes were determined by a combination of PCR and DNA sequencing, as described previously 17 . Briefly, FcγRIIB‐specific PCR was performed in a 2‐‐μl reaction mixture containing 50 ng genomic DNA, 0.5 U Taq polymerase, and FcγRIIB‐specific forward primer (5′‐GGG AAG TAT CGC TGT GAG TTG C‐3′) and reverse primer (5′‐ AGG ATG GAC TTT GGT TAG TGT CTG A‐3′).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent case-control studies of our group [7][8][9][10][11][12][13][14][15][16] in Japanese population are summarized in Table 2 and Fig. 1.…”
Section: Aggressive Periodontitismentioning
confidence: 96%
“…Es sabido que una dificultad para comparar los distintos estudios es la falta de consenso y homogeneidad de criterios, al usarse diferentes definiciones de periodontitis, las que incluyen: periodontitis crónica, estatus periodontal, enfermedad periodontal, periodontitis del adulto, pacientes con periodontitis, enfermedad periodontal refractaria, periodontitis juvenil localizada, periodontitis agresiva localizada/generalizada, además de pacientes resistentes a periodontitis, a lo que se suma el uso de distintas definiciones de umbral diagnóstico o la ausencia de una definición clara de éste. (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) . Por lo mismo, hay coincidencia en que el umbral diagnós-tico, debe ser "preciso, consistente y relativamente precoz en la historia natural de la enfermedad" (1,2) .…”
Section: Test De La Probabilidad Exacta De Fisherunclassified